The Biased Mind How Evolution Shaped our Psychology Including Anecdotes and Tips for Making Sound Decisions - Boutang, Jérôme; De Lara, Michel (Springer International Publishing : Imprint: Springer, 2016)
Using a wealth of anecdotes, data from academic literature, and original research, this very accessible little book highlights how we all struggle to cope with the maelstrom of choices, influences and experiences that come our way. The authors have slogged through piles of dry research papers to provide many wonderful nuggets of information and surprising insights. For example: Why is an upside-down red triangle such a powerful warning sign on the road? What is the best kind of alibi? What makes the number 7 so special? Why is it better to whisper words of love into the left ear? Will that recent marriage last? Why is it that the French eat snails but not slugs? The reader will discover the amazing tools and shortcuts that millennia of evolution have built into our brains. And this knowledge is power! Knowing more about how the human mind connects the dots helps us understand why decision-making is so tricky. With insights from evolutionary psychology, we become better equipped to understand ourselves and others, and to interact and communicate more effectively.